Remarks on KKM Maps and Fixed Point Theorems in Generalized Convex Spaces - Park, Sehie (CUBO, A Mathematical Journal, 2008)
Various types of ðœ™A-spaces (X, D; ðœ™AAâˆˆâŒ©DâŒª) are simply G-convex spaces. Various types of generalized KKM maps on ðœ™A-spaces are simply KKM maps on G-convex spaces. Therefore, our G-convex space theory can be applied to various types of ðœ™A-spaces. As such examples, we obtain KKM type theorems and a very general fixed point theorem on ðœ™A-spaces.